2019
DOI: 10.1021/acs.cgd.9b00570
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and Melting Behavior of Cocoa Butter in Lipid Bodies of Fresh Cacao Beans

Abstract: The present study aims at observing the crystallization and polymorphic behavior of cocoa butter (CB) in fresh cacao beans with DSC and X-ray diffraction techniques. Underlying idea of this study was to relate the necessary conditions of germination of cacao beans to the crystallization of CB, which are present in oil-in-water emulsion droplets (lipid bodies) having 1~2 µm diameters. Different cooling and heating conditions, with rates of 15, 2, 0.5 and 0.1°C/min, were applied to 2 fresh cacao beans and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…SEED 100 cocoa butter crystals (ßV) were provided by Uelzena eG (Uelzen, Germany). The melting peak temperature measured by DSC was 34.0 ± 0.1 °C and the phase transition enthalpy was 132.5 ± 0.7 J/g, which is in line with literature data on the ßV polymorph [ 13 , 14 ] ( Figure S1 ). It needs to be mentioned that other researchers (e.g., [ 12 , 15 ] associated such a melting temperature with polymorph ßVI, but this will not be discussed further.…”
Section: Methodssupporting
confidence: 90%
“…SEED 100 cocoa butter crystals (ßV) were provided by Uelzena eG (Uelzen, Germany). The melting peak temperature measured by DSC was 34.0 ± 0.1 °C and the phase transition enthalpy was 132.5 ± 0.7 J/g, which is in line with literature data on the ßV polymorph [ 13 , 14 ] ( Figure S1 ). It needs to be mentioned that other researchers (e.g., [ 12 , 15 ] associated such a melting temperature with polymorph ßVI, but this will not be discussed further.…”
Section: Methodssupporting
confidence: 90%
“…Since CB is a mixture of TAGs, we must talk about melting range instead of melting temperature [ 55 ]. Bayés-García et al [ 56 ] reported the melting behavior at 2 °C/min of bulk CB and unfermented cocoa beans, finding forms α and ( and of ∼17.5 and 28.6 °C, respectively), values close to those reported in Table 2 . The difference in peak temperature is attributed to a different heating rate [ 57 ].…”
Section: Discussionsupporting
confidence: 70%
“…A shoulder was located at 27.2 ± 1.1 °C, and the end melting temperature was set at 27.7 ± 1.1 °C. These experimental conditions for bulk CB were already reported by our group in previous work …”
Section: Resultssupporting
confidence: 55%
“…Many researchers have investigated the polymorphic crystallization and transformation mechanisms of CB under isothermal and nonisothermal conditions, not only in the bulk state but also under the effects of certain selected additives. , As an example, Loisel et al evaluated the influence of replacing CB partly with its indigenous minor components of tristearoylglycerol (SSS), distearoylglycerol, and stearic acid on chocolate crystallization and determined that the incorporation of distearoylglycerol and stearic acid delayed the formation of SSS crystals and decreased their growth rate to a slight extent. Likewise, a very recent study reported on the effectiveness of the addition of phospholipids at a concentration of the order of 0.1% on the crystallization of CB and commercial chocolate .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation